Validation of Pedsql™ Duchenne Muscular Dystrophy Module (Acute Version 3.0), in Young Children (Age 5-7) - Anas Ali, Muhammad Asif Javed, Hamza Shahzad, Abdul Majid Shahid, Shamoos Saqib, Ayesha Malik, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The goal of this project was to accurately translate the “PedsQLTM 3.0 DMD” Module into Urdu and to assess its validity in health-related quality of life in the Duchenne muscular dystrophy (DMD)” children age 5 to 7 years reported by their parents. Method: The study was conducted with the parents/caregivers of DMD children in Rising Sun Institute, PSRD, Hope,Gosha e Shifa, Special gems, Ghazali Foundation Rawalpindi and DHQ hospital Jhang. Study was cross cultural validation including 56 primary care givers. First of all questionnaire of primary care giver was translated in Urdu by using forward translation, the second step was reconciliation of items; in this the best Urdu translation was selected. Backward translation was completed in the third phase, and a review was conducted to evaluate the full forward-backward procedure in order to produce a final forward translation. Validity & Reliabity were measured. To determine in the internal consistency Cronbach’s Alpha was used Test-Retest reliability was checked. Content Validity Index and Content Validity Ratio were measured through 5 experts. To analyze the collected data SPSS 26 was used. Results: The results showed that in both genders from age 5 to 7 years DMD affects the quality of life of child as reported by parents. The value of Cronbach's alpha was 0.913.After factor analysis KMO was 0.793 and because the p value was less than 0.05, the test was significant. Conclusion: Urdu version of “PedsQLTM Duchenne Muscular Dystrophy Acute Version 3.0(age 5-7) Parent report for young children” is a stable and consistent instrument for assessing quality of life measures of the DMD children and can be applied in Urdu speaking population throughout the world. Keywords: Duchenne Muscular Dystrophy, “PedsQL™ 3.0 DMD Module”, Urdu translation, validity, quality of life.